2020
DOI: 10.2147/idr.s263023
|View full text |Cite
|
Sign up to set email alerts
|

<p>Rifampicin-Resistant <em>Mycobacterium tuberculosis</em> Among Patients with Presumptive Tuberculosis in Addis Ababa, Ethiopia</p>

Abstract: Background: Drug-resistant tuberculosis remains a major public health threat complicating tuberculosis control programs globally. Data on rifampicin resistance (RR), which is a surrogate marker for multidrug resistance, are limited among Ethiopian tuberculosis patients. This study aimed to determine the magnitude of rifampicin-resistant Mycobacterium tuberculosis (RR-MTB) among presumptive tuberculosis patients attending St.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
13
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 40 publications
(65 reference statements)
12
13
3
Order By: Relevance
“…The prevalence of M. tuberculosis among previously treated patients was higher 24.1% than treatment new patients 13.4%, with statistical signi cant difference (P < 0.050). Our nding agrees with studies done at Nepal (27), Hiwot Fana (10) and St. Peter Tuberculosis Specialized Hospital (24). High prevalence of rifampicin resistant M. tuberculosis was also detected among patients who had a history of previously taking anti-tuberculosis drugs (15.4 %) which is comparable with studies from Eastern Uttar Pradesh (12), Nepal 13.79% (27) and Addis Ababa 27.4% (9).This might be due to lack of success from previous tuberculosis treatment history and patients with previously history of taking anti-tuberculosis drugs were more likely to harbor drug-resistant bacilli because of previous exposure of bacilli to TB agents.…”
Section: Associated Factors Of Tuberculosis Infections Among Tb Presumptivesupporting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of M. tuberculosis among previously treated patients was higher 24.1% than treatment new patients 13.4%, with statistical signi cant difference (P < 0.050). Our nding agrees with studies done at Nepal (27), Hiwot Fana (10) and St. Peter Tuberculosis Specialized Hospital (24). High prevalence of rifampicin resistant M. tuberculosis was also detected among patients who had a history of previously taking anti-tuberculosis drugs (15.4 %) which is comparable with studies from Eastern Uttar Pradesh (12), Nepal 13.79% (27) and Addis Ababa 27.4% (9).This might be due to lack of success from previous tuberculosis treatment history and patients with previously history of taking anti-tuberculosis drugs were more likely to harbor drug-resistant bacilli because of previous exposure of bacilli to TB agents.…”
Section: Associated Factors Of Tuberculosis Infections Among Tb Presumptivesupporting
confidence: 92%
“…The prevalence of M. tuberculosis was 17% in males and 13.2% in females but no statistically signi cant association was observed. This study is in agreement with WHO 2020 report (23), India (12), Nigeria (21), St. Peter Tuberculosis Specialized Hospital (24), and Felege Hiwot and Debre Tabor (11). This Variation could be due to difference in community cultural expectations on attempt to get healthcare services, having habit of smoking and alcoholism, high level exposure of males to surrounding.…”
Section: Associated Factors Of Tuberculosis Infections Among Tb Presumptivesupporting
confidence: 91%
“…This result is in agreement with previous studies conducted in Ethiopia. 15 , 23 , 40 Enhanced frequency of MTB in patients having a history of previous treatment indicates high transmission of TB infection in the community. So, serious emphasis should be given for the prevention and control to limit its transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Other study conducted in Addis Ababa also showed that M. tuberculosis was detected in 1714 participants (13.5%) among a total of 12,685 presumptive tuberculosis patients. Of these MTB cases, 169 cases (9.8%) were confirmed to have rifampicin resistant tuberculosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%